THE IMPACT OF MOTIVATIONAL QUOTES IN INSTAGRAM REELS ON MIRROR NEURON ACTIVATION AND COMMUNICATION: A STUDY ON COLLEGE STUDENTS - Dwi Angelica Purba; Fadya Sahira Zulham; Rita Hartati (ADISAM Publisher, 2025)
This study investigates the impact of motivational quotes in Instagram Reels on mirror neuron activation and students’ communication skills. Utilizing a quantitative approach, a survey was conducted with 30 English Literature students from Medan State University. The findings reveal that motivational quotes significantly affect students’ psychological and communicative behavior. A majority of respondents 96.7% reported a shift in perspective after viewing motivational content, and 90% experienced an emotional uplift. Moreover, 93.3% felt inspired to take action, while 83.3% expressed increased confidence in voicing their opinions. Regarding communication, 80% of respondents believed motivational quotes had a long-term positive impact, and the same proportion shared such content with peers or family. Although only 6.7% frequently used motivational quotes in daily conversation, most respondents acknowledged their influence on empathy, confidence, and perspective. These findings suggest that while motivational quotes may not directly transform verbal expression, they play a substantial role in fostering a positive mindset and enhancing internal readiness for communication through mirror neuron stimulation.